Implementasi Kompetensi Kewirausahaan Kepala Madrasah dalam Meningkatkan Mutu Lulusan Madrasah Aliyah - Nurul Inayah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Madrasah heads who have high creative capacities will affect the advancement, improvement, and freedom of madrasas. The motivation behind this examination is to depict marks of enterprising capability for madrasa heads; execution of pioneering ability; and consequences of innovative skill. The methodology utilized is a subjective kind of phenomenology. That s what the outcomes showed: the pioneering capability of madrasah heads at MA Al-Amien 1 Pragaan and MA At-Taufiqiyah Bluto both had great innovative ability; the execution of the enterprising skill of the madrasah head is by arranging, carrying out and assessing; the aftereffects of the pioneering skill of the madrasah head are to create vacationer madrasas, understudies who succeed and instructors and understudies who are enterprising.